Orthodontic Treatment of Two Cases with Mesiodentes: Case Report - Mehmet Bayram; Mete Özer; Çağrı Dinçyürek (Galenos Yayinevi, 2007)
Mesiodentes are the most common supernumerary teeth, found in 0.15% to 1.9% of the population. The cause of mesiodentes is not fully understood, although genetic factors and proliferation of the dental lamina have been implicated. The aim of this study is to present the orthodontic treatment of two cases with mesiodentes. In the first case, two impacted mesiodentes preventing the eruption of the maxillary central incisors were located between the roots of upper lateral incisors in maxillary midline. In the second case, two eruptea mesiodentes were positioned between the crowns of upper central incisors. The treatment of both cases included fixed orthodontic therapy carried out following the extraction of the mesiodentes.